Child Sexual Abuse Awareness, Perception, Experience And Response Among Young Adults: A Comparative Study Among Family Structure - Butt, Sidra Farooq; Jaffri, Noreen; Abbas, Hira (Annals of Human and Social Sciences, 2025)
The aim of this research was to explore about the child abuse, how common it is amongst adolescents, and how to prevent or minimize it so that this generation is mentally well. (Razzak, 2023). In Pakistan, child sexual abuse is a hot subject currently, yet it isim improper or preventable. When a child is taught the proper skills, information, and resources from a young age. For that reason, comprehensive research was required to explore how Pakistani young people perceived, experienced, were conscious of, and responded to child sexual abuse. The purpose of the research is to find out if there will be difference in child sexual abuse awareness, experience, percption and response among young adult based on their family structure. A descriptive study is designed for that to collect data from young adults through convenience sampling, a sample of 320 young adults was taken. Duration of Data Collection was 10 Months. Aging from 20-25 years age range. Survey of child sexual abuse awareness and perception scale (Kailash Satyarthi Children’s Foundation, 2017) was used. Results were analyzed through SPSS 22. Descriptive and Inferential statistics including T-Test and ANOVA was carried out for the Analysis. The results demonstrated significant variation in awareness, perceptions, experiences, and responses to child sexual abuse (CSA) among young adults based on family structure. The Finding of study has major implication in applied field, it will be pilot plotting of thought process of young adults about Child Sexual Abuse, and the similar could add in the direction of making future plans, policies and programs to regulator this obnoxious delinquency in contradiction of children.